1961
DOI: 10.1152/ajplegacy.1961.200.5.1091
|View full text |Cite
|
Sign up to set email alerts
|

Biliary excretion of injected conjugated and unconjugated bilirubin by normal and Gunn rats

Abstract: Conjugated and unconjugated bilirubin were injected intravenously at different times into normal rats and homozygous, jaundiced Gunn rats. As was expected, Gunn rats did not excrete injected unconjugated bilirubin in the bile. After the intravenous injection of conjugated bilirubin into normal rats, approximately twice as much bilirubin appeared in the bile per 100 g of body wt within 10 min than after the injection of comparable amounts of unconjugated bilirubin. This difference probably reflects the time req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
2

Year Published

1966
1966
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(60 citation statements)
references
References 0 publications
6
52
0
2
Order By: Relevance
“…Previous studies have shown that Gunn and normal rats excrete injected conjugated bilirubin at the same rate (7). The present studies show no difference in hepatic subcellular distribution of CB-3H in normal and Gunn rats.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown that Gunn and normal rats excrete injected conjugated bilirubin at the same rate (7). The present studies show no difference in hepatic subcellular distribution of CB-3H in normal and Gunn rats.…”
Section: Discussionsupporting
confidence: 61%
“…The presence of unconjugated bilirubin is not, as others have claimed (49,60,61), simply an artefact produced by hydrolysis of excreted conjugate, since: (a) in this investigation, indirect bilirubin was detected in biles collected freshly on ice and in the dark, conditions that virtually abolished in vitro hydrolysis of bilirubin conjugates; and (b) in an individual bile sample, the per cent of unconjugated bilirubin was unrelated to the rate of hydrolysis of conjugated bilirubin in vitro. Unconjugated bilirubin is found also in the bile of amphibia (62), rats (60,63,64), and humans (65) who cannot synthesize bilirubin glucuronide. Therefore, in contradiction of the current belief (60,66,67) that conjugation is essential for the secretion of bilirubin into the bile canaliculus, it seems likely that unconjugated bilirubin may be secreted also by the liver cell.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we have used synthetic bilirubin glucuronides, 3 H-labeled in the glucuronosyl moiety and stabilized by addition of ascorbate. The use of recombinant MRP2 and the improved methodology for synthesis and stabilization of labeled bilirubin glucuronides yield K m values between 0.5 µmol/L and 0.9 µmol/L ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…An optimal stabilization during the storage in liquid nitrogen under argon was observed at 50 mmol/L ascorbic acid (adjusted to pH 7.4). Under this condition, 3 H-labeled MGB and BGB remained undegraded (Ͼ98%) for up to 28 days in liquid nitrogen. Ascorbate did not affect membrane transport of labeled bilirubin glucuronides described below.…”
Section: Methodsmentioning
confidence: 99%